Conversation’s Premises - Urrea Henao, Jairo (Disertaciones, 2019)
In this essay it is necessary to introduce a concept that is going to be called Premises of the Conversation, taking into account the approach of some argumentation theorists in their proposal about argumentation’s premises. These premises are taken from some language scholars who have observed which structures, rules and ceremonies are outlined for the conversation to take place.As theorists of the new rhetoric suggest, it is not enough, to speak a language to develop a conversation, then, much more is required, and that is, norms and structures that underlie itself; and they add, nobody knows better than the author of Alice in Wonderland.For Carroll's Alice, both in Wonderland and through the looking glass, is almost impossible to strike up a conversation with any of the fantastic characters featured in the two plays. Because in addition to the necessary knowledge about how to use some grammatical rules and a lexicon, it is necessary to know that, when using the language, or as Austin calls it locutionary act, it is also necessary to be aware about the social use of language, because it requires certain conditions, ceremonies and rules that will be explain below.